Biological determinants of immune reconstitution in HIV-infected patients receiving antiretroviral therapy: The role of interleukin 7 and interleukin 7 receptor alpha and microbial translocatioa - Rajasuriar, R.; Booth, D.; Solomon, A.; Chua, K.; Spelman, T.; Gouillou, M.; Schlub, T.E.; Davenport, M.; Crowe, S.; Elliott, J.; Hoy, J.; Fairley, C.; et al. (Elsevier, 2010)
Background. Multiple host factors may influence CD4(+) T cell reconstitution in human immunodeficiency virus (HIV)-infected patients after suppressive antiretroviral therapy (ART). We hypothesized that residual immune activation and polymorphisms in the interleukin 7 (IL-7) receptor alpha (IL-7R alpha) gene were important for immune recovery. Methods. We examined HIV-infected patients receiving suppressive ART (n = 96) for their IL-7R alpha haplotypes and measured levels of lipopolysaccharide (LPS), soluble CD14, and IL-7 in plasma samples collected before and after ART initiation. Levels of soluble IL-7R alpha were measured in HIV-infected patients with IL-7R alpha haplotype 2 (n = 11) and those without IL-7R alpha haplotype 2 (n = 22). Multivariate analysis was used to identify variables associated with faster recovery to CD4(+) T cell counts of > 500 and > 200 cells/mu L. Results. Both LPS and soluble CD14 levels were significantly decreased with ART (P <.001, respectively) but remained elevated compared with uninfected controls. In a multivariate analysis, faster recovery to a CD4(+) T cell count of > 500 cells/mu L was significantly associated with higher baseline CD4(+) T cell count, younger age, lower pre-ART LPS level, higher pre-ART soluble CD14 level, lower pre-ART IL-7 level, and IL-7R alpha haplotype 2 (hazard ratio, 1.50; 95% confidence interval, 1.03-2.19; P = .034). HIV-infected patients with haplotype 2 had significantly lower soluble IL-7R alpha levels compared with those of patients without haplotype 2 (P <.001). Conclusion. Both the extent of immune depletion prior to ART and IL-7R alpha haplotype 2 are important determinants of time to CD4(+) T cell recovery to counts of > 500 cells/mu L.